Cranfield University and University of Maiduguri CubeSat (CUUMcube) for Technology Demonstration: Baseline and Mission Design - Ishaq, M. I.; Kyari, R. A.; Halliru, I.; Amulah, C. N. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
CubeSats are small satellites that can be deployed to orbit to achieve various space mission goals. Lately, there are several CubeSat launch opportunities from the International Space Station (ISS). For University of Maiduguri to be able to bid for such launch opportunities there is a need for a baseline for a spacecraft and a mission design. Thus, this paper using the Systems Engineering approach is a baseline and mission design for a CubeSat using CubeSat COTS (commercial off-the-shelf) components targeting the KiboCUBE opportunity. CUUMcube mission is a technology demonstration mission to fly two payloads, Cranfield’s Acoustic Sensor and De-Orbit Mechanism (DOM). The Acoustic Sensor is a microphone that measures vibrations, it is intended to measure vibrations due to: spacecraft thermal cycling mechanical noise, antenna deployment, Micrometeoroids and Orbital Debris (MMOD) impacts, DOM deployment and changes in acoustic response of spacecraft after deployment of both mechanisms. The DOM is a deployable drag sail, a passive method of removing spacecraft from orbit afterlife in the effort of mitigating space debris. Thus, mission baseline reached after the design is to deploy a 1U CubeSat, to carry two payloads (Cranfield’s Acoustic Sensor and DOM), using COTS components. The deployment of the spacecraft will be from the ISS into an elliptical orbit (perigee: 380km, apogee: 420 km). The ground control stations are COTS component too, where there will be one each in UK and Nigeria. Lastly, 30 mins after deployment into orbit the mission sequence starts from the activation of spacecraft to 24 hours recording mode to monitoring mode by the acoustic sensor to capturing of vibrations. Hence, the antenna and the DOM will be deployed. The DOM will speed the orbit decay of the spacecraft, as a result it will speed the re-entry phase and burn in the process.